Mentorship in Teacher Education: The Impact of Covid-19 in Third World Contexts - Nhemachena, Nancy; Moyo, Mthokozisi (2022)
The Covid-19 pandemic has caused a major upheaval in the teaching and learning process worldwide. It brought about unprecedented challenges to education that has undoubtedly and forever changed the architecture of education. It has altered the traditional roles and relationships of mentors and their protégés as much as it changes the roles of teachers as they shift to e-mentoring after adopting blended education. A precondition for e-mentoring is the availability of and access to Information and Communication Technology gadgets and infrastructure, coupled with digital literacy. Effective mentorship has been hampered by a dearth of ICT infrastructure, the cost of internet services as well as the skills shortage among advanced career teachers who are mostly digital immigrants. This article focuses on the shift to virtual learning and the need of school authorities to actively support e-mentoring programmes within their schools if they are to derive any meaningful benefits from mentoring.